Food Safety Management in the Agri-Food Chain – A Prerequisite for the Production of Sustainable Products - Stoyanova, Antoaneta; Marinova, Velichka; Stoilov, Daniel (Research Papers, 2022)
Nowadays, consumer requirements for goods are diverse and comprehensive - quality and safety, production, in harmony with the environment, delivery in a short terms and at relatively affordable prices. Meeting these needs is aimed at improving food safety policies and strategies by improving control activities and imposing requirements on all participants in the food to agri-food chain. The creation of conditions and traceability between each of the elements of the agri-food chain, as well as the introduction of approaches to ensure food safety is the main EU strategy for achieving sustainability in food production and consumption.The aim of this study is to present through analysis the advantages of existing approaches and mechanisms in food safety management in accordance with the requirements of internationally established standards aimed at the production of sustainable products The benefits of the implementation of food safety management systems in practice are presented, as a factor ensuring the safety of the food offered and giving consumers confidence in the reduced risk associated with their health and life. The methodology used in the study is supported by a systematic review of the requirements set in the standard ISO 22000: 2018 in identifying the processes associated with the creation of the product. The results show that the application of a systematic approach to food safety management is directly related to the strategic issues and objectives of public administration in this area.
Keywords: Quality; Legislation; Agri-food chain; Food; Consumers; Safety